External fixation for the correction of adult post-traumatic deformities. (June 2019) - Goodier, W. David; Calder, Peter R.
Highlights: Any deformity can be defined mathematically in terms of the angular, rotational or translational components. An 'obvious apex' may hide a secondary deformity that either worsens or compensates for the malalignment. There is good evidence that malalignment worsens osteoarthritis and thus should be corrected. There is little evidence that malalignment can cause osteoarthritis de novo. Abstract: Malalignment of the lower limb is a significant factor in the progression of arthritis of the knee and ankle, and correction of deformity can slow the progress and reduce symptoms. It is less clear that malalignment can cause arthritis de novo, but in post traumatic deformity it has been shown that a fracture of the tibia can increase the risk of pain and stiffness of the knee and ankle irrespective of deformity. The management of deformity of the lower limb by external fixation requires a careful systematic method of deformity analysis combining clinical and radiographic assessment is essential to avoid the pitfalls of overlooking potential soft tissue problems, and hidden secondary deformities. External fixators are powerful tools for the correction of deformity, but a sound grounding in deformity analysis is essential.